Realizing Participatory Democracy through Student Presidential Election at Institute Technology Muhammadiyah Sumatra as a Reflection of Indonesian Democracy Values - Rama, Kris Suspon (The Easta Journal Law and Human Rights, 2025)
The election of the Student President (Presma) and Student Vice President (Vice President) at the Institute Technology Muhammadiyah Sumatra (ITMS) reflects the practice of participatory democracy that is in line with Indonesian democratic values. This study aims to analyze the essence, implementation, and praxis of democracy in the context of the election of Presma and Vice President as a miniature of national democracy. The research method applied is a qualitative study with an analytical descriptive approach, involving field data analysis, interviews, and literature studies. The results of the study show that this election not only strengthens student involvement in the decision-making process, but also becomes a forum for learning democracy that reflects active participation, transparency, and accountability. This study recommends improving the electoral system to further strengthen the practice of participatory democracy in the university (campus) environment.